Assessing students' epistemic beliefs related to professional and school science. Issue 6 (13th April 2022) - Voitle, Frauke; Heuckmann, Benedikt; Kampa, Nele; Kremer, Kerstin
ABSTRACT: The school context, like other influences, affects the development of students' epistemic beliefs (EBs), with theoretical conceptualizations suggesting a distinction between EBs related to professional and school science. However, empirical studies rarely address this distinction, and instruments separately assessing these EBs are not available. We address this research gap by providing a new questionnaire that is based on the established instrument by Conley et al. (2004 ) and which uses pairs of analogous items referring to the contexts of professional and school science. We succeeded in simultaneously assessing students' EBs with reliable scales that allow for direct comparisons. Cross-sectional data is reported from a cohort study ( N  = 405) in grades 6 ( n  = 132), 8 ( n  = 167) and 10 ( n  = 106) that showed higher agreement with the scales related to professional science as well as higher agreement in higher grade levels. We further discuss methodological aspects of scale-formation, and highlight promising implementations of our questionnaire that future research could benefit from.